Experimental Study on Ultrahigh Strength Concrete Filled Steel Tube Short Columns under Axial Load - Xiaojun Zhou; Tingmin Mou; Hongyuan Tang; Bikun Fan (Advances in Materials Science and Engineering)
Based on the project of Modaoxi Bridge, an experimental study on the compressive behavior of ultrahigh strength concrete filled steel tube (UHSCFST) short column was conducted. A total of 9 UHSCFST specimens were tested, and the cube strength (fcu) of the core concrete reached 115.4 MPa. Main parameters were the confining factor (ξ=0.608, 0.919, and 1.015), steel ratio (α=14.67%, 20.02%, and 21.98%), and steel strength (fy = 349 MPa, 352 MPa, and 427 MPa). The axially loading test results showed that the visible damage of steel tube occurred under the ultimate load. The higher the confining effect, the less the damage features. And all specimens basically presented a drum-type failure mode. The confining effect of steel tube effectively changed the brittle failure mode of ultrahigh strength concrete (UHSC) and tremendously improved the load bearing capacity and ductility of specimens. Moreover, the higher the steel ratio and steel strength of the specimens, the stronger the confining effect. Meanwhile the excellent mechanical properties will be obtained. Also it is recommended that the UHSCFST prefers Q345 or above strength steel tube to ensure sufficient ductility, and the steel ratio should be more than 20%. Furthermore, the confining effect of steel tubes can improve the ultimate bearing capacity of the ultrahigh strength CFST short columns.